Proceedings of the 6th Unconventional Resources Technology Conference 2018
DOI: 10.15530/urtec-2018-2899671
|View full text |Cite
|
Sign up to set email alerts
|

Barium Sources in Hydraulic Fracturing Systems and Chemical Controls on its Release into Solution

Abstract: The URTeC Technical Program Committee accepted this presentation on the basis of information contained in an abstract submitted by the author(s). The contents of this paper have not been reviewed by URTeC and URTeC does not warrant the accuracy, reliability, or timeliness of any information herein. All information is the responsibility of, and, is subject to corrections by the author(s). Any person or entity that relies on any information obtained from this paper does so at their own risk. The information here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 18 publications
(39 reference statements)
1
26
0
Order By: Relevance
“…Drilling Mud. Experiments by Jew et al 42 suggest that significant amounts of Ba could be released through the interaction of hydraulic fracturing fluids with residual drilling mud barite under downhole conditions, particularly at the low pH characteristic of the initial hydraulic fracturing injection (HCl is added to clear perforations in the cement casing 16 ). To evaluate this hypothesis, we compare the δ 138 Ba of barite from the drilling mud used in MSEEL well MIP-3H to the produced water time series δ 138 Ba data from the same well (Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drilling Mud. Experiments by Jew et al 42 suggest that significant amounts of Ba could be released through the interaction of hydraulic fracturing fluids with residual drilling mud barite under downhole conditions, particularly at the low pH characteristic of the initial hydraulic fracturing injection (HCl is added to clear perforations in the cement casing 16 ). To evaluate this hypothesis, we compare the δ 138 Ba of barite from the drilling mud used in MSEEL well MIP-3H to the produced water time series δ 138 Ba data from the same well (Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…While barite solubility is extremely low under most near-surface environments, 38,39 the presence of high ionic strength fluids and the warm (60−90 °C), 40,41 reducing conditions within the Marcellus Shale could promote barite dissolution. 42 To distinguish among these potential Ba sources and to address the origin of the anomalously high TDS found in Marcellus Shale produced waters, we report stable Ba isotope data from produced water and rock associated with Marcellus Shale exploration. The use of double spike isotope tracers to correct for mass fractionation has allowed precise measurement of stable Ba isotope ratios by multicollector inductively coupled plasma mass spectrometry (MC-ICP-MS) and thermal ionization mass spectrometry (TIMS), and a growing number of Ba isotope studies have been carried out to investigate precipitation, dissolution, and biogenic fractionation of natural and experimental systems, particularly under conditions at or near the Earth's surface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…59 Barium isotopes have helped conrm that dissolution from drilling mud is not a substantial source of Ba to produced waters from the Marcellus shale, but values in produced waters are also not entirely explained by exchangeable or carbonate sources in the shale. 72,73 All of these isotopic studies point toward contributions of Li, Sr, and Ba from sources and processes related to diagenesis rather than water-rock interactions on shorter time scales.…”
Section: Comparison Of Leachates From the Marcellus Shale And Produced Watersmentioning
confidence: 99%
“…These include, for example, the permeability evolution of propped fractures in different types of shales over a range of stress conditions (Voltolini et al, 2017) or the fracture aperture changes and proppant embedment in shales exposed to different types of fracturing fluids (Vankeuren et al, 2017;Moore et al, 2018). Researchers also studied dissolution and precipitation reactions across the fracture-matrix interface (Hakala et al, 2017;Marcon et al, 2017;Harrison et al, 2017;Jew et al, 2017a, Jew et al, 2017bJew et al, 2018; and demonstrated that properties of the shale matrix and fractures can be affected by mineral precipitation arising from the injected fluids (fracture to rock) and chemical alterations to the shale itself (matrix to fracture). In ultra-low permeability rocks, especially those with > 20 wt.% clay, geochemical reactions can reduce overall permeability by more than 40% (Allali et al, 2018).…”
Section: Tough Modeling Of Productionmentioning
confidence: 99%